Ethics education during medical residency training and biopsychosocial approach - Gençer, Mehmet Ziya; Arıca, Seçil; Ağırman, Ege (Journal of Surgery and Medicine, 2018)
While a rapid specialization process has started within the field of medicine along with the rapid advancement in technology, particularly for the last bicentenary, the significance of an integrated approach towards the patient in that process has been realized once again. Medical ethics and ethics education have appeared as two interconnected notions from ancient times to present that each new specialization area integrates idiosyncratic ethical priorities into the field of medicine with the advancement in information. Even if ethics courses given during basic medical education list the core values, it is not all that wrong to say that the ethical approach has kind of a perpetual structure shaped by the practices within the physician-patient relationships. Moreover, different notions and values exist in different specialties. However, the ideal approach in a physician-patient relationship which has been recognized in the world today is a patient-centered approach apart from the emergency cases in which patients have a risk of death.